Kinetic Modeling of Peroxydisulfate Pre-Treatment of Algae Slurry (Pasir Gudang, Malaysia) for Increasing Methane Generation from Anaerobic Digestion: Fertilizer Recovery - Nurul Islam Siddique, Md.; Zaied, B.K.; Zamri Bin Ibrahim, Mohd.; Wan Nik, W.B.; Binti Ali, Noraaini; Shila Rasit, Nazaitul (Asian Journal of Chemistry, 2022)
This study looked into the possibility of using peroxydisulfate pretreatment to enhance biogas production from anaerobic fermentation of algal slurry. The results demonstrate that a peroxydisulfate added system with a dose of 0.02 g peroxydisulfate/g algal sludge TSS produces the most accumulative methane after 61 days of fermentation. At 0.02, 0.03, 0.06, 0.2, 0.3, 0.6, and 1.2 g peroxydisulfate/g algal sludge TSS cumulative methane generation was 1.16, 1.09, 1.15, 1.14, 1.09, 0.77, and 0.16 times higher than control. After 120 minutes of pre-treatment, the SCOD in the system continued to rise when the peroxydisulfate dosage was enhanced. To simulate the methane yield, a one-substrate model might be utilized. After dosing with peroxydisulfate, the hydrolysis rate reduced, and the maximum resultant and anticipated cumulative methane output was achieved with 0.02 g peroxydisulfate/g algal sludge TSS. After digestion, microcystin-LR in algae slurry was mostly eliminated. Heavy metals could be released from algae cells into the effluent as a result of the greater peroxydisulfate dosage. From the fermented effluent, sludge recapture was 0.09 m3 sludge/m3. The supplementation of peroxydisulfate to algae slurry may boost cumulative methane generation while also lowering microcystin-LR levels.